Determinants of long-acting contraceptive utilization among married women of reproductive age in Aneded district, Ethiopia: a case–control study - Habtamu, Abebe (BMC Res Notes, 2019)
OBJECTIVES: To identify the determinants of long-acting contraceptive utilization among married women of reproductive age in Aneded district, northwestern Ethiopia. Unmatched case control study was conducted from May 1, 2018 to June 30, 2018. One hundred forty-five households with married reproductive age women who have used long-acting family planning for more than a year (cases) and 290 households with married reproductive age women who have never used long-acting family planning (controls) were selected by systematic random sampling in each kebele (the smallest administrative units of Ethiopia). RESULT: In this study, 145 cases and 290 controls participated. Independent positive predictors of utilization of long-acting family planning among married women reproductive age were: primary education level [AOR = 6.99, 95% CI 3.7–13.7], first discussion with providers [AOR = 2.64, 95% CI 1.6–4.5], told what to do if they experience the side effect [AOR = 3.2, 95% CI 1.7–5.9], know the source of long-acting family planning methods [AOR = 3.4, 95% CI 2.01–5.82] and discussion with health professionals [AOR = 2.07, 95% CI 1.2–3.5]. Encouraging women education at least at primary level and advocating the minimal side effect of long-acting contraceptive are recommended to improve long-acting family planning utilization.